2012
DOI: 10.1073/pnas.1113770109
|View full text |Cite
|
Sign up to set email alerts
|

A unique series of reversibly switchable fluorescent proteins with beneficial properties for various applications

Abstract: Reversibly switchable fluorescent proteins (RSFPs) have attracted widespread interest for emerging techniques including repeated tracking of protein behavior and superresolution microscopy. Among the limited number of RSFPs available, only Dronpa is widely employed for most cell biology applications due to its monomeric and other favorable photochemical properties. Here we developed a series of monomeric green RSFPs with beneficial optical characteristics such as high photon output per switch, high photostabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 37 publications
1
123
0
2
Order By: Relevance
“…We also compared rsKame with another green PS-FP, mGeos-M, that has similar photo-physical properties (25). However, mGeos-M exhibits more significant basal photoactivation by 488 nm than rsKame ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also compared rsKame with another green PS-FP, mGeos-M, that has similar photo-physical properties (25). However, mGeos-M exhibits more significant basal photoactivation by 488 nm than rsKame ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we compare four properties of PAFPs that are critical for superresolution imaging and report two new PAFPs that exhibit excellent performance in all four properties. (14), mEos3.2 (15), tdEos (16), mKikGR (17), PAmCherry (18), PAtagRFP (19), mMaple (20), PSCFP2 (13,21), Dronpa (22), and mGeosM (23). From this screen, we found that none of these PAFPs was simultaneously optimal in all four criteria described above.…”
mentioning
confidence: 86%
“…The protocol used was described previously (16). Purified protein of Skylan-NS was first photoswitched to its off states using a 60-mW, 488-nm LED.…”
Section: Methodsmentioning
confidence: 99%